DETEKSI DINI KOMPLIKASI KEHAMILAN, PERILAKU HIDUP BERSIH DAN SEHAT SERTA DETEKSI DINI GANGGUAN PERTUMBUHAN DAN PERKEMBANGAN BAYI DAN BALITA DI WILAYAH KERJA PUSKESMAS PEGAMBIRAN KOTA PADANG - Aldina Ayunda Insani; Erda Mutiara; Fitrisia Amelin; Yulizawati Yulizawati; Lusiana El Sinta Bustami; Feni Andriani (LPPM (Institute for Research and Community Services) Universitas Andalas Padang, 2019)
Puskesmas Pegambiran is located in Lubuk Begalung Sub-district, Padang City has five villages with a pregnancy complication rate of 19.9% and neonatal complications of 11.74% (2016). The general objective that will be achieved is to increase the number of better health degrees for pregnant women, infants, toddlers, and pre-school age children through promotive and preventive activities. The method used is by conducting surveys and interviews, conduct counseling, demonstrate clean and healthy living habits, anthropometric measurements of infants, toddlers, and pre-school children, observation, pregnancy checks, hemoglobin checks, and counseling. The results obtained were counseling and demonstrations on clean and healthy living behaviors in pre-school age children at Alya Zahira Kindergarten, which all students could participate in and run smoothly. 98% of kindergarten students demonstrated healthy hygiene habits, including washing hands, brushing teeth, and mentioning healthy snacks. Anthropometric measurements of infants and toddlers and pre-school age children showed that weight for age was within normal limits, height/length according to age, and expected limits. 3.7% thin and short toddlers and 1.2% of toddlers have speech delays, 1.2% children under five with a history of epilepsy, and need further treatment, so referrals are made. 1.2% of children under five were referred to because they did not recognize colors. All pregnant women (100%) have normal hemoglobin levels (10 g / dl), and pregnancy conditions are appropriate for their gestational age. It is hoped that further community service activities will be carried out by applying the partnership midwifery practice model (mentoring) to the above targets for several months. There are changes in behavior patterns for promotive and preventive actions that have been given.